Monitoring and optimization of the microcirculation during CPB - Murkin, John M. (Journal of Thoracic Disease, 2019)
In this review the impact of cardiopulmonary bypass (CPB) on the microcirculation is discussed. The impact of conventional non-pulsatile perfusion is contrasted with the microcirculatory impact of pulsatile CPB which is associated with better preservation of microcirculatory function. Evidence that alterations in microcirculatory function that persist following cardiac surgery are associated with adverse clinical outcomes is reviewed. Recent studies using novel techniques employing near infrared reflectance spectroscopy (NIRS) and sublingual microscopy to explore alterations in microcirculatory function during CPB are reviewed and the implications of these observations for studies investigating minimally invasive extracorporeal circulation (MiECC) are discussed.